1989
DOI: 10.1186/1297-9686-21-1-107
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the deleted hobo element Th in Eurasian populations of Drosophila melanogaster

Abstract: Summary — Molecular analysis has revealed the presence of a specific deletion-derivative hobo element, the Th element, in all current strains of Drosophila melanogaster examined throughout the Eurasian continent. The Th element is characterized by an internal deletion of 1.5 kb as compared to the complete hobo element. The presence of this element in natural populations raises the question of its possible role in the regulation of the hobo system. Drosophila-transposable elements -hobo-populations Résumé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…We found no hobo elements in the Hikone-R strain, collected in 1952, but we did detect them in the Hikone- hobo elements in Japanese populations of D. melanogaster K Kikuno et al H and Mino-H strains, collected in 1957. This is consistent with the hypothesis that hobo transposable elements invaded the D. melanogaster genome in the mid1950s in America, France, USSR, China, and Africa (Periquet et al, 1989a(Periquet et al, , b, 1990Boussy and Daniels, 1991;Pascual and Periquet, 1991). Around 1950, in HikoneCity large quantities of DDT and pyrethrum were used for several years to kill mosquitoes for malaria control, and the insecticide-resistant strain, Hikone-R (E), was isolated (Ogaki and Tsukamoto, 1953).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We found no hobo elements in the Hikone-R strain, collected in 1952, but we did detect them in the Hikone- hobo elements in Japanese populations of D. melanogaster K Kikuno et al H and Mino-H strains, collected in 1957. This is consistent with the hypothesis that hobo transposable elements invaded the D. melanogaster genome in the mid1950s in America, France, USSR, China, and Africa (Periquet et al, 1989a(Periquet et al, , b, 1990Boussy and Daniels, 1991;Pascual and Periquet, 1991). Around 1950, in HikoneCity large quantities of DDT and pyrethrum were used for several years to kill mosquitoes for malaria control, and the insecticide-resistant strain, Hikone-R (E), was isolated (Ogaki and Tsukamoto, 1953).…”
Section: Discussionsupporting
confidence: 87%
“…The deletion of the 1.6 kb fragments is the central portion of the full-sized element. The 2.2 and 2.0 kb deleted hobo elements have not been obviously present in the surveys of populations from other countries (Periquet et al, 1989a(Periquet et al, , b, 1990Boussy and Daniels, 1991;Pascual and Periquet, 1991;Kim and Kim, 1999). Therefore, they seem to be defective hobo derivatives unique to Japanese Drosophila populations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, all recently derived and present-day populations that have been tested carry numerous hobo elements. A recent study has shown a high frequency of a derivative-deleted element of 15 kb (Th), in all populations tested from France to China, and in the Americas, a distribution which is highly similar to that of KP elements (Periquet et a!., 1989b).…”
Section: Resultsmentioning
confidence: 90%